2017
DOI: 10.4081/ijfs.2017.6612
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic antimicrobial resistance profile of isolates causing clinical mastitis in dairy animals

Abstract: Mastitis is the most frequent and costly disease of lactating animals and is associated with a significant reduction in milk yield, increased cost and culling. Early and specific antibiotic based treatment reduces the severity of the disease. Over the years the extensive use of antimicrobials has led to increase antimicrobial resistance. The present study was designed to investigate the prevalence of microorganisms responsible for mastitis and their antimicrobial resistance pattern. A total of 282 milk samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 24 publications
(32 reference statements)
1
21
1
1
Order By: Relevance
“…and a similar finding was reported by Mishra et al (2017) [9]. The pattern of phenotypic resistance for the tested antimicrobial drugs in this study was similar to the pattern reported in various other studies by [10], [11], [12] and [13].…”
Section: Discussionsupporting
confidence: 92%
“…and a similar finding was reported by Mishra et al (2017) [9]. The pattern of phenotypic resistance for the tested antimicrobial drugs in this study was similar to the pattern reported in various other studies by [10], [11], [12] and [13].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, our study showed that 42.86% of the retail samples analysed do not respond to the standards established by the EU, and moreover, 3 samples tested positive for enterotoxins. Despite S. aureus being one of the most common causes of mastitis in dairy animals [25] and one of the major foodborne pathogens worldwide [26], food poisoning outbreak linked to raw milk cheese consumption has been rarely reported [27]. Differently, it is generally believed that coagulase-negative Staphylococci, such as S. epidermidis and S. warneri, isolated in two positive samples, have low pathogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published on antibiotic resistant bacteria in sheep milk, both in milk from individual sheep, and in bulk milk, and also in raw sheep milk cheese. Studies were focused on resistant zoonotic bacteria, commensal bacteria, mastitis-causing bacteria, and specific resistances, including methicillin-resistant S. aureus (MRSA), extended-spectrum beta-lactamase (ESBL)-producing Gram-negative bacteria, and vancomycin-resistant enterococci (VRE) (Abdalhamed et al, 2018;Abo-Shama, 2014;Alian et al, 2012;Ariza-Miguel et al, 2014;Azara et al, 2017;Burriel, 1997;Carfora et al, 2016;Ceniti et al, 2017;Corrente et al, 2003;Giacinti et al, 2017;JimĂ©nez et al, 2013;Lollai et al, 2016;Macori et al, 2017;Mousavi et al, 2014;Obaidat et al, 2018;Onni et al, 2011;Ortigosa et al, 2008;Sanciu et al, 2012;Solomakos et al, 2009;Spanu et al, 2012Spanu et al, , 2014. Comparing literature data on antibiotic resistant bacteria in raw sheep milk is complicated because of several differences, e.q.…”
Section: Antibiotic Resistancementioning
confidence: 99%